SOCIAL SOLIDARITY AND ITS TYPES IN THE KINGDOM OF GRANADA (897 AH / 1492 AD) - Mohammed Marzouk; Thyab Ahmed (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2022)
The study of social interdependence in the Kingdom of Granada (897 AH-1492 AD) is a Solidarity and social welfare in the Kingdom of Granada is a distinctive feature of this kingdom. Although this kingdom was surrounded by dangers and difficulties, it was able to cope with all circumstances. Its resistance was not limited to the military side, but I feared another form represented by the solidarity and social care provided by the sultans of the Kingdom of Granada to their subjects. Solidarity and so cial care in the Kingdom of Granada included all aspects of food, military, health, religious and educational life. During the reception of the displaced from the areas where the war is taking place, and the contribution to the construction of forts and castles, as for the health aspect, the people of the community participated in building hospitals and health homes, and the sultans established some of them, and some of the people donated to spend on hospitals, while on the religious side, Many of the people of Granada donated to build and restore mosques, and many residents also donated to build schools, science houses, and spend on students. That is, social solidarity in the Kingdom of Granada was contributed by all members of society, and it included all aspects of life in Granada.